(untitled) (Research, Society and Development, 2020)
The presence and contamination of groundwater by nitrate is still a little studied subject mainly focusing on public health. Thus, this work aims to identify and evaluate the sources of nitrate contamination of drinking water in Minas Gerais and São Paulo, based on field research and analyzes of the Water Quality Surveillance Information System for Human Consumption ( Sisagua), which is a tool of the National Water Quality Surveillance Program (Vigiagua) to manage the health risks associated with the quality of water intended for human consumption. The results of the evaluation of nitrate concentrations in the waters distributed and consumed by the population in Minas Gerais come mainly from pastures, followed by crops, in São Paulo predominantly from industries followed by pastures.